Mastering mathematics - Buckwell, G. D. (Macmillan master series, 1997)
The second edition of this popular book has been fully revised. Geoff Buckwell combines a practical approach with a clear straightforward style. * A complete, self-contained course for individual study or classroom use * Investigations to help you explore topics in a more practical way * Problems at the end of chapters to consolidate what you have learned * Explains pencil and paper techniques in full * Illustrations and revision materials for enjoyable learning.